CLONING AND EXPRESSION OF A LIPASE GENE FROM PSEUDOMONAS AERUGINOSA INTO E.coli - & Khalifa, Auda (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Fifteen local isolates of Pseudomonas were obtained from several sources such as soil, water and some high-fat foods (Meat, olives, coconuts, etc.). The ability of isolates to produce lipase was measured by the size of clear zone on Tween 20 solid medium and by measuring the enzymatic activity and specific activity. Isolate M3 (as named in this study) was found to be the most efficient for the production of the lipase with enzymatic activity reached 56.6 U/ml and specific activity of 305.94 U/mg. This isolate was identified through genetic analysis of the 16S rRNA gene. and it was shown that the isolate M3 belongs to Pseudomonas aeruginosa with 99% similarity. The DNA of isolate M3 was extracted and lipase gene was amplified through PCR technique, then purified and cloned into E.coli DH5α cells first using pTG19-T plasmid, and expressed in E.coli Bl21 with expression vector pet-28a. The activity of lipase from transformed E.coli Bl21 was 196.6 U/ml and the specific activity 618.2 U/mg.